2015
DOI: 10.1109/tpwrs.2014.2388193
|View full text |Cite
|
Sign up to set email alerts
|

Load Decomposition at Smart Meters Level Using Eigenloads Approach

Abstract: The deployment of the advanced metering infrastructure (AMI) in distribution systems provides an excellent opportunity for load monitoring applications. Load decomposition can be done at the smart meters level, providing a better understanding of the load behavior at near-real-time. In this paper, loads' current and voltage waveforms are processed offline to form a comprehensive library. This library consists of a set of measurements projected onto the eigenloads space. Eigenloads are basically the eigenvector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 31 publications
(44 reference statements)
0
22
0
1
Order By: Relevance
“…In terms of CR and RMSE, the compression performances of SAE (with fine-tuning) and several other methods are compared on case 1, including PCA [24], DWT [25,26] and k-SVD [7,21]. Figure 10 displays the results.…”
Section: Performance Of Saementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of CR and RMSE, the compression performances of SAE (with fine-tuning) and several other methods are compared on case 1, including PCA [24], DWT [25,26] and k-SVD [7,21]. Figure 10 displays the results.…”
Section: Performance Of Saementioning
confidence: 99%
“…Users should be classified into more specific and meaningful types. In non-intrusive load identification, the readings are investigated to match the household appliances [24,31], e.g., refrigerator and air conditioner.…”
Section: Introductionmentioning
confidence: 99%
“…Several NILM systems have been studied, which could roughly be divided into two categories. One is the method applying mathematical optimization [8,10,11,13,29], and the other one is based on pattern recognition [14][15][16][17][18][19][20][21][22][23][24][25]30].…”
Section: Related Workmentioning
confidence: 99%
“…In 2015, Ahmadi et al [29] first merged the loads' current and voltage waveforms into a comprehensive library. Then they found that each load of the appliance is similar to the Face recognition [33].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation